Poverty Rates and the Factors Influencing Poverty Alleviation: A Case Study in the Province of West Kalimantan, Indonesia - Akhmad Yani; Restiatun Restiatun; Romi Suradi (Universitas Muhammadiyah Ponorogo, 2022)
There is a trend of decreasing the poverty rate in Indonesia. But in the Province of West Kalimantan, there are still five districts with poverty rates that are above the average national rate, namely Melawi, Landak, Ketapang, Sintang, and North Kayong districts. The purpose of this study is to estimate the relationship between government transfers which are proxied by the amount of GAT (General Allocation Transfer) Funds, economic growth, and the quality of human resources in terms of education and health which are proxied by the average years of schooling and public-health insurance membership. Once these factors can be identified, it is hoped that the government will find it easier to reduce poverty levels. Based on Nested Test, model that passes the goodness of fit test is The Common Effect model so this model is used in estimating and interpreting in this research. It shows that there is no difference in the behavior of the research variables, either between time or between individuals. The findings of this study that the economic growth variable is not significant in reducing the poverty level, the variable of literacy level have a significantly negative effect on the poverty level, the variable of public-health insurance membership has significantly positive on the poverty level, and the central government transfer variable proxied by GAT has significantly positive effect significant to the poverty level.